Xeroderma Pigmentosum- Eye Changes - Bhaduri Gautam; Banerjee Anita (Wolters Kluwer Medknow Publications, 2002)
Xeroderma pigmentosum is a rare hereditary and fatal disease of the skin. Ocular involvement is known to occur in 80% of cases. Two brothers of a family with cutaneous and ocular involvement are reported.